The effect of aqueous caustic and various acid treatments on the removal of mineral matter in asphaltite - Doymaz, I.; Gulen, J.; Piskin, S.; Toprak, S. (TAYLOR & FRANCIS INC, 2007)
In this present study, high mineral matter ( ash) asphaltites from Silopi, Southeastern Anatolia, Turkey were investigated using aqueous sodium hydroxide followed by various mineral acids such as HNO3, HCl, H2SO4, and HF. The extraction with 5% NaOH followed by leaching with 10% H2SO4 plus 40% HF was the optimum approach for chemical cleaning of the asphaltite and the maximum degree of the demineralization was found as 59.56%. At the same time, the calorific value increased to 20.86% according to the original sample. In addition, the spectrometric analyses of treated asphaltite samples were performed by FTIR and X-ray diffraction.
Keywords: asphaltite; demineralization; FTIR; mineral matter; X-ray diffraction; CHEMICAL DEMINERALIZATION; SIRNAK-ASPHALTITE; ALKALI TREATMENT; COAL; LIGNITES; SULFUR; TURKEY; Energy & Fuels; Engineering; Environmental Sciences & Ecology